Corrosion in Titanium dental implants – a review - Yarram, Anusha; KSV, Ramesh; G, Narasimha Rao; SA, Yasmeen; MC, Suresh Sajjan; AV, Ramaraju (International Journal of Dental Materials, 2019)
Titanium (Ti) is the most widely used biomaterial for dental implants as it exhibits excellent mechanical properties and biocompatibility. The biocompatibility of titanium is related to thin, protective surface titanium dioxide (TiO2) layer, which forms a boundary at the implant-biological medium interface, reducing its reactivity with the surrounding biological environment and prevents corrosion. However, the metallic materials used as implants are susceptible to corrosion due to variations in the internal electrolyte environment. The surface oxide layer can be destroyed during insertion of implant or micro-motion between implant and bone under loading conditions. The localized destruction causes corrosion of the implant and induces leak of metallic particles or ions into surrounding tissues. The presence of metallic particles in peri-implant soft and hard tissues may be due to frictional wear or corrosion, or simultaneous occurrence wear and corrosion which is known as tribocorrosion. The released metal ions may remain in the intercellular spaces near the site where they were released or may be taken up by macrophages, or they can migrate systemically. This review article highlights various aspects of corrosion, biological response to corrosion products and prevention of corrosion of titanium dental implants.